Collateral damage of COVID-19 pandemic in private healthcare centres of Argentina - Bozovich, Gerardo Edgar (2020)
To contain the coronavirus pandemic (COVID-19), a strict nationwide lockdown has been enforced and the health systems have been reorganized to deal with this entity. During this period, changes in the care of non-infectious diseases have been observed. Our aim was to describe the impact of the COVID-19 pandemic in the care of non-communicable diseases. A structured retrospective survey was carried out in 31 healthcare centers affiliated with the Asociación de Clínicas, Sanatorios y Hospitales Privados de la República Argentina y Cámara de Entidades de Diagnóstico y Tratamiento. We compared data for April 2019 versus April 2020 regarding emergency room consultations, hospital admissions, invasive procedures and treatments, and bed occupancy. In April 2020, we observed a decrease in emergency room visits (75%) and hospitalizations (48%). A 62% decrease in admissions was noted for angina pectoris and acute coronary syndromes and a 46% decrease in admissions for stroke and transient ischemic attack. A meaningful decrease was found in coronary angioplasties (59%) and total percutaneous interventions (65%), and also a decrease in general surgeries (73%), and cardiac surgeries (58%). Although social distancing measures are a key public health strategy to flatten the infection curve, the observed decrease in medical visits and interventions may impact negatively on cardiovascular, cerebrovascular and cancer related morbidity and mortality. A collective effort is required to avoid the unintended consequences and collateral damage of the COVID-19 pandemic.